2002
DOI: 10.1046/j.1365-8711.2000.03818.x
|View full text |Cite
|
Sign up to set email alerts
|

SiC2 in carbon stars: Merrill-Sanford absorption bands between 4100 and 5500 Å

Abstract: Observations and identifications of the Merrill–Sanford bands of the silicon dicarbide molecule are reported for a range of N and J stars. The data were recorded at 0.8−1.6 Å resolution between 4100 and 5500 Å. A full description of the assignments and spectral features in the stars is given. The spectra are characterized by absorption from the ground vibrational level (0, 0, 0) and from higher‐lying vibrational levels involving one quantum of excitation in ν1, and up to two quanta in ν2 and ν3, giving rise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…These molecular bands are identified between 4100−5500 Å in carbon stars (e.g. Sarre et al 2000;Yamashita & Utsumi 1968;and McKellar 1947). In fact we detect extra-absorptions around 4867 and 4906 Å, not present in the other stars of the sample, which coincides with the position of some band heads of this molecule.…”
Section: Analysis: the Extragalactic Carbon Stars And Their Chemical supporting
confidence: 63%
“…These molecular bands are identified between 4100−5500 Å in carbon stars (e.g. Sarre et al 2000;Yamashita & Utsumi 1968;and McKellar 1947). In fact we detect extra-absorptions around 4867 and 4906 Å, not present in the other stars of the sample, which coincides with the position of some band heads of this molecule.…”
Section: Analysis: the Extragalactic Carbon Stars And Their Chemical supporting
confidence: 63%
“…Many of the bands have double heads corresponding to ‘R’ and ‘Q’ rotational band structure, and in these cases we have two sets of the pairs of values for the wavelengths of the bandhead and of the peak emission intensity in Table 4. Agreement with the wavelengths of the same features measured on the absorption spectra of N stars (Sarre et al 2000) is better for the stronger features.…”
Section: Molecular Emission Features Of Iras 12311−3509mentioning
confidence: 51%
“…The star IRAS 12311−3509 is a most unusual object with an optical spectrum dominated by the Merrill–Sanford emission bands of SiC 2 . These bands are more commonly seen in absorption in cool N‐type carbon stars (see Sarre, Hurst & Lloyd Evans 2000). This star was discovered in a project aimed at identifying possible new RV Tauri stars selected from the IRAS Point Source Catalogue (Beichman et al 1988) on the basis of their characteristic colours in the [12]–[25], [25]–[60] diagram: they have red [12]–[25] and an excess at 60 μm relative to the majority of such stars (Lloyd Evans 1985; Raveendran 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The MS bands are sufficiently strong that they have been given their own index by Keenan (1993) in his revised classification scheme for carbon stars. More recently, a full assignment of the MS bands to individual vibrational transitions in the SiC 2 molecule has been given by Sarre, Hurst & Lloyd Evans (2000). These authors also provide a description of the historical development of the study of MS bands in astronomical and laboratory spectra.…”
Section: Introductionmentioning
confidence: 99%
“…MS bands are not seen in the majority of carbon stars, but when present they are usually quite strong, most probably because they are critically dependent on temperature – provided the star has sufficient carbon in its atmosphere (see Tsuji 1981; Barnbaum et al 1996). Barnbaum et al (1996) also noted that MS bands are most often observed in J‐type carbon stars; but this remark may be influenced by the fact that J‐type stars have more flux in the blue and consequently are more favourable for the study of MS bands (Sarre et al 2000).…”
Section: Introductionmentioning
confidence: 99%